2016
DOI: 10.3748/wjg.v22.i24.5609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of anesthetization by dezocine combined with propofol for indolent colonoscopy

Abstract: This study revealed that dezocine combined with propofol can be successfully used for the anesthetization of indolent colonoscopy patients without pain and should be widely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Following lateral positioning, an oxygen inhalation mask was administered immediately at a rate of 3L/min. The patients in the alfentanil and propofol (AP) group were administered alfentanil (Yichang Humanwell Pharmaceutical, Co., Ltd., China, 13S03051) 10 μg/kg and propofol (Corden Pharma S.P.A., RX061) 2 mg/kg [22][23][24][25]. Patients in remimazolam groups were received alfentanil 10 μg/kg, followed by remimazolam besylate (Yichang Humanwell Pharmaceutical, Co., Ltd., China, 70,705,021) 0.1 mg/ kg (AR1 group), 0.15 mg/kg (AR2 group), or 0.2 mg/kg (AR3 group).…”
Section: Anesthesia Management and Interventionmentioning
confidence: 99%
“…Following lateral positioning, an oxygen inhalation mask was administered immediately at a rate of 3L/min. The patients in the alfentanil and propofol (AP) group were administered alfentanil (Yichang Humanwell Pharmaceutical, Co., Ltd., China, 13S03051) 10 μg/kg and propofol (Corden Pharma S.P.A., RX061) 2 mg/kg [22][23][24][25]. Patients in remimazolam groups were received alfentanil 10 μg/kg, followed by remimazolam besylate (Yichang Humanwell Pharmaceutical, Co., Ltd., China, 70,705,021) 0.1 mg/ kg (AR1 group), 0.15 mg/kg (AR2 group), or 0.2 mg/kg (AR3 group).…”
Section: Anesthesia Management and Interventionmentioning
confidence: 99%
“…Another study among health mice indicated that dezocine antagonizes morphine analgesia on acute nociception upon simultaneous administration [ 23 ]. A study conducted by the Xu et al [ 24 ] showed that dezocine combined with propofol can be successfully used for the anesthetization of indolent colonoscopy patients without pain and should be widely used. Therefore, our meta-analysis obtained a consistent result with the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has a sedative effect, while both dezocine and fentanyl exert analgesic effects. Dezocine activates κ receptor in cerebral cortex, leading to slow onset and long duration of analgesia [3,7,8], Table 3: Serum levels of inflammation-related endocrine hormones before and after colonoscopy examination (mean ± SD) while fentanyl brings about fast onset but shortlived analgesia through activation of the μ and δ receptors in the central nervous system (CNS). Thus the use of fentanyl after colonoscopy examination is not ideal.…”
Section: Discussionmentioning
confidence: 99%